cis-acting sequences involved in human immunodeficiency virus type 1 RNA packaging. - Kaye, J F (1995)
We have previously described a series of human immunodeficiency virus type 1-based vectors in which efficient RNA encapsidation appeared to correlate with the presence of a 1.1-kb env gene fragment encompassing the Rev-responsive element (RRE). In this report, we explore in detail the role of the RRE and flanking env sequences in vector expression and RNA encapsidation. The analysis of a new series of vectors containing deletions within the env fragment failed to identify a discrete packaging signal, although the loss of certain sequences reduced packaging efficiency three- to fourfold. Complete removal of the env fragment resulted in a 100-fold decrease in the vector transduction titer but did not abolish RNA encapsidation. We conclude that the RRE and 3' env sequences are not essential for human immunodeficiency virus type 1 vector encapsidation but may be important in vectors in which a heterologous gene has been placed adjacent to the 5' packaging signal, potentially disrupting its structure.